Pemeriksaan Pediculus Humanus Capitis Pada Anak Sekolah Dasar Di Pesantren Hidayatullah Kota Palangka Raya Tahun 2023 : Pediculus Humanus Capitis In Examination in Primary School Children at Hidayatullah Boarding School Palangka Raya In 2023 - Nanda, Putri; Sartika, Fera; Ramadhani, Fitria Hariati; Rahmah, Windya Nazmatur (Borneo Journal of Medical Laboratory Technology, 2023)
Head lice (Pediculus humanus capitis) are parasites that live on the hair and scalp of humans by sucking blood from the human scalp. The transmission of head lice can occur directly (hair to hair) and indirectly through shared accessories. A pesantren is one of the places where several people gather in the same location, and this is a primary factor in the spread of Pediculus humanus capitis infection. The research objective is to determine the number of children infected with Pediculus humanus capitis. The research method used is descriptive. The sample in this study consisted of 14 individuals taken using total sampling technique. The research results showed that there were 4 students (29%) infected with Pediculus humanus capitis at Pesantren Hidayatullah in Palangka Raya City, and 10 students (71%) were not infected with Pediculus humanus capitis. The positive results are believed to be due to the habit of using hair accessories such as shared hair combs, which increase the occurrence of Pediculus humanus capitis infection.